Sneaky Pete - Milios, Rita.; Martin, Clovis (Chicago : Childrens Press, 1989)
Sneaky Pete proves why he's the champion of Hide and Seek.
Includes a word list.
School Library Journal.
1.5.
1.5
K-3
P-2.
Keywords: Hide-and-seek -- Fiction; Stories in rhyme; Hide-and-seek -- Fiction; Stories in rhyme